To Pave or Not to Pave : Developing a Framework for Systematic Decision-Making in the Choice of Paving Technologies for Rural Roads - World Bank (World Bank, Washington, DC, 2021)
Investments in road infrastructure as a means for granting access and mobility have been an important part of the World Bank's strategy of fightingpoverty and increasing shared prosperity since its inception. Studies suggest that road infrastructure triggers economic development through reductions in transport and trade costs, which in turn leads to upgraded access to markets and social services (health, education, administrative, leisure); fosters agricultural production; alters production decisions; stimulates off-farm diversification; and catalyzes other income-earning opportunities. As a variate means to different ends, farmers use rural roads to take their produce to markets; workers to travel to their places of employment; tourists to head to their destinations; the pregnant and sick to seek urgent medical attention; children to get to school; transporters to make their deliveries; and families and friends to visit their loved ones. Bridging Africa's infrastructure gap is key to overcoming the continent’s development challenges. Road infrastructure is a key component of this effort. Inadequate road infrastructure retards economic growth potential by undermining the export competitiveness of agricultural produce and other manufactured goods; curtails the opportunity for employment and business development; and impedes human development efforts in health and education. World Bank estimates indicate that Africa needs 93 billion dollars a year for its infrastructure sectors, with about two-thirds of it required for new investment in physical infrastructure, and the other third for maintenance and operations. Of this amount, road infrastructure is expected to take up about 18 billion dollars.